Investigating the role of mycorrhizal fungi and associated bacteria in promoting growth of citrus seedlings - Sitole, Phumeza (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
South Africa is the world's second largest exporter of fresh citrus and is ranked 14th in citrus production. Fungal pathogens such as Phytophthora and Pythium cause economic losses as a result of root rot and brown rot. Mycorrhizal fungi are specialized members of the fungal community forming a mutualistic relationship with plant roots. Mycorrhizal fungal structures are known to associate with other soil microorganisms and these may contribute to improved plant growth. A diverse group of bacteria that interact with the mycorrhizal fungi are known as Mycorrhizal Helper Bacteria (MHB). The aim of this study was to investigate the role of arbuscular mycorrhiza and associated bacteria isolated from spores and determine whether they had any plant growth promoting potential. A total of 19 bacteria were isolated from arbuscular mycorrhizal spores and were molecularly identified as belonging to several Bacillus, Micrococcus, Onchrobactrum and Staphylococcus sp. All bacterial isolates were tested for plant growth promotion abilities. One Bacillus isolate was able to solubilise phosphate. Four isolates Micrococcus sp, Micrococcus leteus, Ochrobacterum sp and Ochrobacterum antropi were able to produce Indole Acetic Acid and three isolates showed potential to reduce growth of Phytophthora nicotianae, P. citrocola and P. citrophthora in in vitro plate cultures. Further tests using culture supernatants of the Bacillus sp, Micrococcus sp and Bacillus cereus confirmed their ability to inhibit or reduce growth of the three Phytophthora species in a 96 well bioassay. Bacillus sp and Bacillus cereus were able to inhibit Phytophthora spp by 95 to 100 % and Micrococcus spp was able to decrease pathogen growth by 60 to 94 %. These bacterial isolates were further evaluated for plant growth promoting abilities on citrus rough lemon seedlings alone or in combination with arbuscular mycorrhizal inoculum. Bacterial and mycorrhizal inoculants influence the increase in shoot and root biomass. Bacillus cereus in combination with mycorrhizal inoculum significantly increased seedling shoot to root ratio while root biomass was significantly increased with mycorrhizal inoculation. Due to the short duration of the trial mycorrhizal colonisation could not be assessed. It is evident that selected combinations of bacteria and mycorrhizal fungi could promote citrus seedling growth and potentially improve seedling health. Further studies under nursery conditions are recommended.
Keywords: Mycorrhizal fungi; Citrus -- South Africa; Citrus -- Diseases and pests -- Biological control -- South Africa; Fungi as biological pest control agents; Bacteria; Phytophthora; Pythium; Indoleacetic acid